THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE OF THERAPEUTIC COMMUNICATION AND THE LEVEL OF CONFIDENCE IN THE PRACTICE FIELD FOR PROFESSIONAL NURSE STUDENTS AT STIKES MEDISTRA INDONESIA - Sukarno, Nurhasanah (Rena Cipta Mandiri, 2022)
The level of confidence can have an impact on one's communication because it is closely related to one's ability to communicate. Very effective communication skills make it easier for nursing students to solve patient problems and communication facilitates the selection of interventions both medically and psychologically. Nursing communication is known as therapeutic communication which has an important role in nursing services and can also be interpreted as a determinant of the success of the services to be provided. The purpose of the study was to determine the relationship between the level of therapeutic communication with the level of confidence in the practice field for the students of the STIKes Medistra Indonesia. The quantitative research method is analytic with a cross-sectional approach, sampling using a probability sampling technique of random sampling with a total of 98 students. The conclusion is that there is a relationship between the level of knowledge of therapeutic communication with the level of confidence in the practice field at the STIKes Medistra Indonesia.